Enhancing Oxidative Stability and Nutritional Quality of Flaxseed Oil Using Apricot, Sesame, and Black Cumin Oil Blends - Dino Muhović; Gorica Cvijanović; Marija Bajagić; Lato Pezo; Lazar Pejić; Biljana Rabrenović (Foods)
There is an unmet need for an affordable, high-quality, and non-thermally processed source of omega-3 fatty acids. Cold-pressed flaxseed oil comes closest to meeting these criteria. Flaxseed oil is also subject to rapid oxidative degradation. Sesame, black cumin, and apricot kernel oils are already used as functional foods and are more resistant to oxidative degradation. GC, HPLC, DPPH, the Folin−Ciocalteu method, and OXITEST were applied to the four cold-pressed oils and their binary blends with flaxseed oil. The fatty acid profile showed that the dominant fatty acid in flaxseed oil was linolenic acid with a content of 52.27 ± 0.17%, while oleic acid dominated in apricot kernel oil (69.45 ± 0.18%) and linoleic acid (58.80 ± 0.07%) in black cumin oil, while sesame oil was characterized by approximately equal proportions of oleic (42.21 ± 0.20%) and linoleic acids (43.37 ± 0.07%). The content of oleic acid showed a moderate, statistically significant correlation with the oxidative stability of oils and blends. The antioxidant capacity of flaxseed oil (25 ± 1.4 μmol TE/g) was most strongly influenced by the addition of black cumin oil (75 ± 3.5 μmol TE/g), so that the highest antioxidant capacity was achieved by the blend with an addition of 50% of this oil (57.5 ± 2.4 μmol TE/g). Oxidative stability tests show that apricot kernel oil stabilizes flaxseed oil the most and increases the oxidative stability of the blend by up to 60%.